Bioactivity of bovine lung hydrolysates prepared using papain, pepsin, and Alcalase. Issue 6 (28th July 2017) - O'Sullivan, Siobhan M.; Lafarga, Tomas; Hayes, Maria; O'Brien, Nora M.
Abstract: Bovine lung tissue was hydrolyzed using three different proteases, papain, pepsin, or Alcalase, to generate hydrolysates. Hydrolysates showed little antioxidant activity in noncellular or cellular assays. The anti‐inflammatory activity of hydrolysates was assessed in RAW264.7 macrophages and Jurkat T cells. Treatment with the Alcalase hydrolysate significantly decreased the production of the pro‐inflammatory cytokines interleukin (IL)‐6 and IL‐1β in a dose dependent manner in RAW264.7 cells. Nitric oxide production also significantly decreased following treatment with this hydrolysate. The papain hydrolysate decreased IL‐6, IL‐1β, and NO production in RAW264.7 cells and IL‐2 production in Jurkat T cells. However, the decrease was likely due to cytotoxicity of this hydrolysate toward these cell lines. The pepsin hydrolysate had no effect on cytokine production in RAW264.7 cells and only slightly decreased IL‐2 production in Jurkat T cells. Practical applications: Meat production generates large amounts of protein rich co‐products, which are often discarded as waste or sold as low value animal feeds. The enzymatic hydrolysis of these protein co‐products may produce hydrolysates that are capable of reducing oxidation or inflammation. Novel hydrolysates were generated from the hydrolysis of bovine lung and results from this study indicate that the hydrolysis of bovine lung using the commercially available protease Alcalase may have potential as an anti‐inflammatory agent.